(untitled) (Journal of Economic Research & Business Administration, 2018)
Personnel management is the main factor of modern society economic success. This significantly changes the very concept of “human resources management” - it goes from a simple prompt solution to the determination of problems arising the definition of people future needs, as well as the development of both their labor and creative potential. In this regard, it should be emphasized that in business, especially in large-scale one Personnel management is focused on solving strategic tasks of the organization innovative development, in other words, its goals and principles must comply with the organization basic strategic concept, and the function of personnel management must be taken into account when developing the organization strategy. The aim of the study is to determine the new technologies effectiveness in public administration. This is called service-oriented thinking. In short, service systems are the location of systems that create value and include people sharing information, technology and organizations, as well as language, measures, models, laws, etc. The main carrier of new competitive ideas, solutions, non-standard tasks or new ways of solving standard problems is the personnel. Creation of an efficient and effective system of public administration is a necessary condition for ensuring the dynamic social and economic development of our country. Therefore, the number one task remains to improve the effectiveness of public administration, strict observance of the rule of law by state officials, and the provision of high-quality public services to the public. Thus, the urgency of researching innovative methods of the personnel management system in a state institution is due to the need for timely formation and development of innovative mechanisms for making managerial decisions that are adequate to the requirements of the modern economy, scientific and technical and information progress. Analyzing the foreign experience of the above countries, it should be noted a number of features that are of practical interest and can be taken into account in the process of improving the public service system of Kazakhstan: - in the countries examined, the professionalization of the state apparatus is carried out on an ongoing basis; - flexible methods of human resources management (personnel management); - there are mechanisms for transferring the best employees with experience between the public and private sectors. Analyzing the experience of foreign countries, it is necessary to determine the level of public confidence in the system of competitive selection and the level of confidence of civil servants and citizens in the mechanism for implementing the principles of meritocracy, that is, raising the career ladder with merit. During the development of innovative methods, knowledge of the program being implemented in the public service is acquired; knowledge of the best personnel technologies used in the modern public service of foreign countries; knowledge of the possibilities and limitations of the use of traditional and innovative human resources management tools in the civil service management practice; the ability to make a reasonable choice of a specific staff tool, taking into account the purposes of its application, as well as the specifics of the given situation; skills of developing procedures and documents by the personnel department. This is called service-oriented thinking. In short, service systems are the location of systems that create value and include people, share information, technologies and organizations, as well as language, measures, models, laws, and so on.